Mating, oviposition behaviour and biology of hogplum beetle (Bangladesh Journal of Agricultural Research, 2017)
Experiments were conducted to observe mating and oviposition behabiour as well as biology of hog-plum beetle. Results revealed that the average mating frequency, mating duration and mating interval were 11.2, 30.5 hours and 60.3 hours, respectively. The highest number of eggs per clusters was on leaf rachis followed by young stem. The mean number of eggs per cluster was 15.70 while the length and breadth of an egg was 1.95 mm and 0.60 mm, respectively. The mean duration of 1st, 2nd, 3rd and 4th instar larvae were 3.80, 3.40, 3.70 and 3.00 days, respectively. The mean pupal period was 22.74 days. The female beetle lived longer (48.30 days) than the male (45.10 days). The size of female beetle was larger (15.30 mm) than male (11.96 mm). The mean length of antennae was 7.42 mm. The length of fore, mid and hind legs were 9.20, 9.50 and 11.70 mm, respectively. Hind wings were larger (16.10 mm length and 7.85 mm breadth) than fore wings (12.38 mm length and 5.30 mm breadth).Bangladesh J. Agril. Res. 42(3): 503-508, September 2017